Pragmatism and its influence on Chemistry teaching - Cañas Quinto, Emily Viviana; Gutierrez Pincay , Carolina Stefania; Prieto Lainez , Melina Isabel (Revista Minerva, 2023)
This study investigates the influence of pragmatism in chemistry education, focusing on the integration of experiential learning to enhance pedagogy. Through a systematic literature review and empirical analysis, the research explores how pragmatism-driven strategies improve student engagement and learning outcomes. The research included an in-depth analysis of peer-reviewed articles, conference papers, and relevant books from leading databases. The results highlight that experiential learning, driven by pragmatism, significantly improves student engagement and conceptual understanding. The study concludes that the integration of pragmatism in chemistry education leads to a more effective learning process, fostering critical thinking and problem-solving skills in students
Keywords: Pragmatism; chemistry teaching; experiential learning; student engagement; pedagogical strategies; learning outcomes